LEXICAL PREFERENCES OF UZBEK EFL LEARNERS: A COMPARISON OF BRITISH AND AMERICAN ENGLISH - Aminjonov, Avazjon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This study examines Uzbek EFL learners’ preferences for British English and American English vocabulary and relates these choices to classroom norms and everyday exposure. In Uzbekistan, many English textbooks and teaching materials are based on British English, but learners often encounter American English through social media and entertainment. A voluntary online questionnaire was completed by 167 English major undergraduates at Kokand University. The vocabulary section included 20 paired items, and participants selected the word they use most often. Across 3,340 selections, American English forms were chosen slightly more often (1,812; 54.25%) than British English forms (1,528; 45.75%), although preferences differed sharply by item. A paired-samples t-test was applied to the multiple-choice vocabulary task at the item level (20 pairs) and did not show a significant overall difference across items, t(19) = 0.92, p = .371. Attitude items showed moderate agreement that students hear American English more often on social media (M = 3.14) and that teachers mostly use British English (M = 3.31), while perceived ability to notice differences was closer to neutral (M = 2.89). Overall, the findings point to hybrid lexical use shaped by parallel input streams. Pedagogical implications focus on raising awareness of lexical variation and teaching practical strategies for maintaining consistency in assessed academic writing.